The Macroeconomy of Central America - Offerdal, Erik.; Rennhack, Robert (Washington, D.C. : International Monetary Fund, 2004)
Opportunities for growth and investment in Central America could well improve in the coming years, as the region's ties with the world economy grow closer. This integration, however, also presents important challenges for economic policy to ensure that growth can be sustained and can benefit the poor. This book stresses the importance of keeping fiscal policy on a sustainable path; strengthening public investment in basic infrastructure, primary health care, and primary and secondary education; and managing the risks associated with partial dollarization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet